The Impact of the TNI Manunggal Village Building Program (TMMD) on the Socio-Economic Community Towards Empowerment of Regional Defense: - (International Journal of Scientific Research and Management (IJSRM), 2022)
This study aims to identify and analyze the impact felt by the community from the implementation of the TNI Manunggal Community Building (TMMD) program in terms of economic, social, and territorial defense aspects. The research method used is a descriptive method with a qualitative approach. The results showed that the TMMD Program organized by the TNI to support national development in rural areas had a very significant impact on the economic, social, and regional defense aspects. The output to be achieved in the TMMD program has been successfully achieved. With the TNI Manunggal Building Village program, the living standards of rural communities can be increased so that they can support as a source of strength in implementing the Universal People’s Defense System (Sishanta).